2019
DOI: 10.1021/acs.chemmater.8b04531
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Formation of Vertical Orientation in Two-dimensional Metal Halide Perovskite Thin Films

Abstract: Metal halide perovskites have demonstrated strong potential for optoelectronic applications. Particularly, two-dimensional (2D) perovskites have emerged to be promising materials due to their tunable properties and superior stability compared to their three-dimensional counterparts. For high device performance, 2D perovskites need a vertical crystallographic orientation with respect to the electrodes to achieve efficient charge transport. However, the vertical orientation is difficult to achieve with various c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
147
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(150 citation statements)
references
References 54 publications
3
147
0
Order By: Relevance
“…When Lewis bases are not employed, we suggest that the perovskite crystal seeds form directly upon DMF evaporation and then self‐assemble, presumably maximizing their van der Walls interactions between each other, leading to a preferential orientation either of parallel or of perpendicular to substrate . Our observation that the crystal phases are oriented perpendicular to the substrate may indicate that crystallization for the large‐ n phases proceeds more significantly at the interface with atmosphere rather than with the substrate . It is unclear why fast crystallization caused by antisolvent dripping could induce vertical orientation in the annealed film.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…When Lewis bases are not employed, we suggest that the perovskite crystal seeds form directly upon DMF evaporation and then self‐assemble, presumably maximizing their van der Walls interactions between each other, leading to a preferential orientation either of parallel or of perpendicular to substrate . Our observation that the crystal phases are oriented perpendicular to the substrate may indicate that crystallization for the large‐ n phases proceeds more significantly at the interface with atmosphere rather than with the substrate . It is unclear why fast crystallization caused by antisolvent dripping could induce vertical orientation in the annealed film.…”
Section: Resultsmentioning
confidence: 91%
“…It is worth mentioning that our thin films were deposited by antisolvent (chlorobenzene) dripping during spin‐coating in a water‐free environment, because those can also affect phase orientation . The previous studies reported that for large‐ n phases, the orientation of the perovskite seeds produced at the interface with atmosphere strongly influences that of the phases in the resulting films . When Lewis bases are not employed, we suggest that the perovskite crystal seeds form directly upon DMF evaporation and then self‐assemble, presumably maximizing their van der Walls interactions between each other, leading to a preferential orientation either of parallel or of perpendicular to substrate .…”
Section: Resultsmentioning
confidence: 95%
“…[7,21,23,40,41] Devices with the configuration of glass/ITO/antisolvent-bathed perovskite films/Au were fabricated. A space-charge-limited current (SCLC) analysis was performed to characterize the trap density of the perovskite films, because it was anticipated that a larger grain size and oriented grain growth could reduce the intra-and inter-granular defect densities.…”
Section: Resultsmentioning
confidence: 99%
“…[17] Controlling the crystal orientation of large-area perovskite films can provide the opportunity to achieve the maximum PCE. [22][23][24][25][26] Herein, we propose a simple cold antisolvent bathing method allowing large-area compatible crystallization control during methyl ammonium lead triiodide (MAPbI 3 ) perovskite film growth. [21] There have been numerous attempts to develop nucleation and growthcontrolling strategies for obtaining perovskite films with a high degree of crystal orientation.…”
Section: Doi: 101002/aenm201901719mentioning
confidence: 99%
“…The mixed grain orientation can be explained given the understanding that these materials nucleate at the liquid–air interface. [ 23 ] Whereas in n = 1 bilayer RPPs, the organic layers will tend to align along the surface with the bulky ligands perpendicular to the surface, with a single diammonium ligand, the dangling bonds of the second ammonium group inhibit this simple alignment, inducing a mixed grain orientation.…”
Section: Characterizationmentioning
confidence: 99%